Argumentation Ab Homine in Philosophy - Leal, Fernando (Informal Logic, 2021)
Argumentation that uses the beliefs of one’s opponents to refute them is well known (ad hominem in the classical sense). This paper proposes that there is a hitherto unnoticed counterpart to it, to be called ab homine, in which speakers/writers argue through the manner in which they deliver a message. Since the manner of delivery can never be turned into a premise or premises, this form of argumentation—although somewhat resembling Aristotle’s ethos—is much closer to the peculiar force of Socratic elenchos.